2012
DOI: 10.1186/1478-811x-10-25
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial secretion of CTGF as a cell-type specific response to LPA and TGF-β in human tubular epithelial cells

Abstract: BackgroundIncreased expression of the pro-fibrotic protein connective tissue growth factor (CTGF) has been detected in injured kidneys and elevated urinary levels of CTGF are discussed as prognostic marker of chronic kidney disease. There is evidence that epithelial cells lining the renal tubular system contribute to uptake and secretion of CTGF. However, the role of different types of tubular epithelial cells in these processes so far has not been addressed in primary cultures of human cells.ResultsTubular ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…The link between ERK and CTGF seems to be dependent on the stimulus and cell type, as it is not observed under all conditions (e.g., Samarakoon et al, 2009). In tubular epithelial cells, however, ERK activation has been shown by us and others as one of the important signaling pathways of CTGF expression (Phanish et al, 2005;Zuehlke et al, 2012). Next we addressed the question whether activation of ERK was a direct consequence of inhibition of Aurora kinases.…”
Section: Discussionmentioning
confidence: 95%
“…The link between ERK and CTGF seems to be dependent on the stimulus and cell type, as it is not observed under all conditions (e.g., Samarakoon et al, 2009). In tubular epithelial cells, however, ERK activation has been shown by us and others as one of the important signaling pathways of CTGF expression (Phanish et al, 2005;Zuehlke et al, 2012). Next we addressed the question whether activation of ERK was a direct consequence of inhibition of Aurora kinases.…”
Section: Discussionmentioning
confidence: 95%
“…The experiment has revealed that CTGF expression was increased in tubular epithelial cells in multiple forms of CKD. 17,18 However, CTGF, a 36-38-kDa small molecule, can filter across glomerular basement membrane and be present in the tubular fluid in pharmacologically active concentrations. Therefore, tubular epithelial cells not only express and secrete CTGF but are also exposed to CTGF from the glomerulus.…”
Section: Discussionmentioning
confidence: 99%
“…Because CTGF can be both secreted and membrane bound, western blot analysis of the cell lysate may not reflect the total protein amount produced when compared to mRNA expression. While in mesangial cells it is bound to the cell surface (49), it has been shown that in hepatocellular carcinoma cells, a fraction of the produced protein remains cell-bound (38). This may explain why our mRNA and protein expression data do not necessarily correlate.…”
Section: Discussionmentioning
confidence: 54%